Design of Chemically Stable Organic Perovskite Quantum Dots for Micropatterned Light‐Emitting Diodes through Kinetic Control of a Cross‐Linkable Ligand System. Issue 23 (3rd May 2021) - Lee, Hanleem; Jeong, Ji Won; So, Mo Geun; Jung, Gun Young; Lee, Chang‐Lyoul
Abstract: Perovskite quantum dot (QD) light‐emitting diodes (PeLEDs) are ideal for next‐generation display applications because of their excellent color purity, high efficiency, and cost‐effective fabrication. However, developing a technology for high‐resolution multicolor patterning of perovskite QDs remains challenging, owing to the chemical instability of these materials. To overcome these issues, in this work, the generation of surface defects is prevented by controlling the ligand‐binding kinetics using a stable ligand system (Stable LS). The crystalline reconstruction of perovskite QDs after addition of the Stable LS results in an ≈18% increase in their photoluminescence quantum yield in solution and it also improves the ambient stability of the perovskite QD solution. Moreover, the perovskite QDs with Stable LS can undergo cross‐linking under UV irradiation. The tightly bridged perovskite QDs effectively prevent moisture‐assisted ligand dissociation in film state due to the increased hydrophobicity and restricted movement of the cross‐linked surface ligands. Thus, the cross‐linked perovskite QD film shows improved chemical/environmental stability without substantial deterioration in optoelectrical properties. As a result, a white electroluminescent device with high resolution (≈1 μm) is successfully fabricated by inkjet printing using green and red perovskite QDs. Abstract : The fast degradation of perovskite quantum dots (QDs) prevents the development of multicolor patterning technologies using these materials. Therefore, novel ligand systems for microsized EL device fabrication, which protect perovskite QDs from degradation through the binding kinetic control of surface ligands, are developed. The present system remains stable in various chemical environments, without critical deterioration of optical and electrical properties.